Combination therapy with tocilizumab and corticosteroids for aged patients with severe COVID-19 pneumonia: A single-center retrospective study. (April 2021) - López-Medrano, Francisco; Pérez-Jacoiste Asín, María Asunción; Fernández-Ruiz, Mario; Carretero, Octavio; Lalueza, Antonio; Maestro de la Calle, Guillermo; Caro, José Manuel; de la Calle, Cristina; Catalán, Mercedes; García-García, Rocío; Martínez-López, Joaquín; Origüen, Julia; et al.
Highlights: An increasing number of immunomodulatory therapies are being tested for COVID-19. A survival benefit has been shown with the use of corticosteroids. The role of combination therapy with corticosteroids and tocilizumab is unclear. This study analyzed a single-center cohort of patients aged ≥65 years with severe COVID-19. The sequential use of corticosteroids and tocilizumab was associated with better outcomes. Abstract: Background: The role of combination immunomodulatory therapy with systemic corticosteroids and tocilizumab (TCZ) for aged patients with COVID-19-associated cytokine release syndrome remains unclear. Methods: A retrospective single-center study was conducted on consecutive patients aged ≥65 years who developed severe COVID-19 between 03 March and 01 May 2020 and were treated with corticosteroids at various doses (methylprednisolone 0.5 mg/kg/12 h to 250 mg/24 h), either alone (CS group) or associated with intravenous tocilizumab (400–600 mg, one to three doses) (CS-TCZ group). The primary outcome was all-cause mortality by day +14, whereas secondary outcomes included mortality by day +28 and clinical improvement (discharge and/or a ≥2 point decrease on a 6-point ordinal scale) by day +14. Propensity score (PS)-based adjustment and inverse probability of treatment weights (IPTW) were applied. Results: Totals of 181 and 80 patients were included in the CS and CS-TCZ groups, respectively. All-cause 14-day mortality was lower in the CS-TCZ group, both in the PS-adjusted (hazard ratio [HR]: 0.34; 95% confidence interval [CI]: 0.17–0.68; P  = 0.002) and IPTW-weighted models (odds ratio [OR]: 0.38; 95% CI: 0.21–0.68; P  = 0.001). This protective effect was also observed for 28-day mortality (PS-adjusted HR: 0.38; 95% CI: 0.21–0.72; P  = 0.003). Clinical improvement by day +14 was higher in the CS-TCZ group with IPTW analysis only (OR: 2.26; 95% CI: 1.49–3.41; P  < 0.001). The occurrence of secondary infection was similar between both groups. Conclusions: The combination of corticosteroids and TCZ was associated with better outcomes among patients aged ≥65 years with severe COVID-19.